EARLY TREATMENT OF A PRESCHOOL CHILD’S CROSSBITE USING DIRECT DENTAL TRACKS, THREE-YEAR FOLLOW-UP - CLINICAL CASE REPORT - Ciarcia, Ana Carolina Costa da Mota; Cavalcanti, Marcos Fernando Xisto Braga; Diomede , Francesca; Pugliesi, Maria Priscila de Souza Monteiro; Olivan , Silvia Regina Garcia; Altavista , Olga Maria (Brazilian Journal of Implantology and Health Sciences, 2026)
Background The treatment of young children can be difficult even for trained professionals. The prevalence of malocclusion in this phase of development can vary widely according to the population studied, and more specifically, to their genetic heritage. However, physical stimuli, such as habits, can also lead to a lack of proportionality in the craniofacial skeleton. Case Report This paper reports the treatment of C. M. R., a 4-year-old female preschooler, who presented with anterior and posterior crossbites, second molars exhibiting mesial terminal steps, and a negative overject. This case was treated using Direct Dental Tracks to correct the malocclusion, and the patient was followed for three years. Final considerations This treatment was successful in restoring her craniofacial growth and development to the normal individual pattern. The patient is ready to begin the follow-up phase of occlusal development using Planas functional orthopedic appliances until final occlusion is established with the second molars in occlusion.